Jejunal obstruction due to ischemic stricture: an unusual presentation - Huda, Tanweerul; Pandya, Bharati (International Surgery Journal, 2019)
Background: The most common causes of mechanical small bowel obstruction are postoperative adhesions and hernias. Other etiologies of small bowel obstruction include, diseases intrinsic to the wall of the small intestine, like tumors, strictures, intramural hematoma and processes that cause intraluminal obstruction like intussusception, gallstones, foreign bodies etc. Ischaemic enteritis is a rare etiology, reported only in about 0.1% of cases. Ischaemic strictures of the small bowel are a result of decreased blood supply to the small intestine. They require surgical intervention for their management. Methods: Author presented a 40 year-old diabetic female who presented with upper GI obstruction of 2month duration. Her history of illnesses included stroke, myocardial infarction and a transient episode of intestinal obstruction occurring simultaneously 3years ago. On investigations, she was found to have an occlusive distal jejunal stricture. Author studied the literature for the various management options and selected the most appropriate one for her. Results: Exploratory laparotomy with resection and end to end anastomosis of the jejunal segment was done. The histopathology of the segment revealed ischaemic enteritis with large vessel blockade causing stricture. The patient had an uneventful post op recovery and is asymptomatic two months since. Conclusions: Ischaemic enteritis results in small intestinal obstruction due to intestinal stenosis in its chronic phase. Diagnostic delay is due to the differential diagnoses and missing out on the transient phase of early ischemia.